2016
DOI: 10.1039/c5sc04557f
|View full text |Cite
|
Sign up to set email alerts
|

Observation of quantum dynamical resonances in near cold inelastic collisions of astrophysical molecules

Abstract: Quantum resonances in inelastic collisions, predicted by theory and detected at low energies in a crossed-beam experiment, are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 52 publications
0
43
0
1
Order By: Relevance
“…97 In crossed molecular beam experiments with laboratory frame velocities v 1 and v 2 and reduced mass µ for the colliding species, the collision energy in the center-of-mass frame (the relative translational energy) is given in terms of the relative velocity…”
Section: Experimental Studies Of Cold and Ultracold Reactions Andmentioning
confidence: 99%
See 1 more Smart Citation
“…97 In crossed molecular beam experiments with laboratory frame velocities v 1 and v 2 and reduced mass µ for the colliding species, the collision energy in the center-of-mass frame (the relative translational energy) is given in terms of the relative velocity…”
Section: Experimental Studies Of Cold and Ultracold Reactions Andmentioning
confidence: 99%
“…The discrepancy was attributed in part to the restriction of a single adiabatic electronic potential energy surface (PES) for the scattering calculations. Several studies of inelastic collisions have been reported 97 [99][100][101] Ortho-H 2 (nuclear spin = 1) and para-H 2 (nuclear spin = 0) refer to two nuclear spin states of H 2 characterized by odd and even rotational levels, respectively. At these temperatures, several partial waves contribute leading to broad resonances in the energy dependence of the cross sections.…”
Section: Experimental Studies Of Cold and Ultracold Reactions Andmentioning
confidence: 99%
“…[47][48][49][50] Another type of experiment that is not discussed herein concerns the opticalt rappingo fu ltracold molecules, such as KRb, to study ultracold collisions. [30,37,45,46,54,55] [30,37,45,46,54,55] …”
Section: Cold Collisionsmentioning
confidence: 99%
“…Experimental data are sparse but are critical for benchmarking theoretical methods [8][9][10] . Numerical solution of the Schrödinger equation offers the best hope for generating the bulk of the needed data.…”
Section: Introductionmentioning
confidence: 99%